"Limiting power cycling stress in power MOSFETs by active thermal control". (August 2020) - Magnone, Paolo; Abedini, Hossein; Petucco, Andrea
Abstract: In this work we propose a system which is able to actively control the temperature of a power MOSFET, in order to limit the temperature swing and hence to reduce the power/thermal cycling effect. To this purpose a dedicated driving circuit, allowing to control the gate voltage of the switching device under investigation, is used in a synchronous buck converter. Therefore, power losses can be modulated in order to reach the desired temperature through self-heating effects. The implemented control system is able to compensate the non-linear relationship between the gate voltage and the on-resistance. Moreover, to improve the response of the system, a predictor has been implemented, having the capability of on-line tuning the thermal resistance of the device. Experimental results are reported to demonstrate the suitability of this solution to control the temperature in the semiconductor device. The reduction of temperature swing under power and thermal cycling is also demonstrated. Highlights: Active thermal control is implemented to limit thermal cycling in power MOSFETs. Gate voltage is modulated to control the internal power dissipation of the device. The control system is based on a double (voltage and temperature) loop approach. A predictor is used with an on-line thermal resistance tuning algorithm. The reduction of temperature cycling allows improving the device reliability.